Pickleball Transcends the Generations in Southwest Indiana: A University and Area Agency on Aging Partnership Changing the Face of Aging. Issue 3 (2nd July 2016) - Reynolds, Erin; Daum, David N.; Frimming, Renee; Ehlman, Katie
ABSTRACT: An intergenerational pickleball tournament was designed to create a setting wherein older adults interact with undergraduate students, generating an intergenerational learning experience. Teams of older adults were recruited through the local Area Agency on Aging and paired with undergraduate students to provide an opportunity for older adults to share their love and knowledge of pickleball with a younger generation. The students interacted with active, older adults in an activity that connected the generations. An informal evaluation, completed by students, and process-evaluative measures revealed the successes of the tournament. Interdisciplinary approaches to this intergenerational experience brought both academic and community partners together for the creation and implementation of the event. This practice-based paper includes a rationale for tournament implementation, describes program goals and implementation details, and includes a theoretical framework for application. Additionally, the authors utilize student feedback and process-evaluation measures to discuss implications for practice and relevance to other locales.